Millennial Leadership Style and Organisational Culture on Employee Performance with Job Satisfaction as a Mediating Variable (Research at Gammara Hotel) - Angelica, Andary; Wanasida, Albert Surya (Transpublika Publisher, 2025)
The primary objective of this research is to examine how the leadership style of millennials and the culture within the organisation impact the performance of employees, with job satisfaction acting as a mediator at Gammara Hotel. The uniqueness of this study is in its investigation of how millennial leadership styles interact with various other organisational aspects within the Indonesian hospitality sector. A quantitative research approach was utilised, involving 157 participants who were chosen through non-probability accidental sampling. Data analysis was conducted using the Partial Least Squares Structural Equation Modelling (PLS-SEM) technique. The findings indicated that the leadership approach of millennials positively impacts employee performance, with no direct effect from organisational culture. Millennial leadership style was also found to influence job satisfaction positively, in contrast to an adverse impact from organisational culture. Despite this, job satisfaction was not found to be a mediator between the two variables and employee performance. These results emphasise the significance of adopting a cooperative and flexible millennial leadership style to enhance employee performance, while considering the presence of a supportive organisational culture.